Budowa ciała siatkarzy na różnych poziomach sportowych = Body build of volleyball players on different sport levels - Pietraszewska, Jadwiga; Stachoń, Aleksandra; Burdukiewicz, Anna; Andrzejewska, Justyna; Sieroń, Adrian (Journal of Education, Health and Sport, 2016)
Pietraszewska Jadwiga, Stachoń Aleksandra, Burdukiewicz Anna, Andrzejewska Justyna, Sieroń Adrian. Budowa ciała siatkarzy na różnych poziomach sportowych = Body build of volleyball players on different sport levels. Journal of Education, Health and Sport. 2016;6(6):543-552. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.56532 http://ojs.ukw.edu.pl/index.php/johs/article/view/3641 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.05.2016. Revised 25.06.2016. Accepted: 28.06.2016. Budowa ciała siatkarzy na różnych poziomach sportowych Body build of volleyball players on different sport levels Jadwiga Pietraszewska1, Aleksandra Stachoń1, Anna Burdukiewicz1, Justyna Andrzejewska1, Adrian Sieroń2 1 Zakład Antropologii Fizycznej , Akademia Wychowania Fizycznego we Wrocławiu 2Akademia Wychowania Fizycznego we Wrocławiu, student Adres do korespondencji: Jadwiga Pietraszewska Akademia Wychowania Fizycznego we Wrocławiu Zakład Antropologii Fizycznej Al. I.J. Paderewskiego 35, P-2 51-612 Wrocław Telefon: + 48 71 347 33 44 E-mail: jadwiga.pietraszewska@awf.wroc.pl Słowa kluczowe: budowa ciała, siatkarze, poziom sportowy. Streszczenie: Sukces sportowy jest uwarunkowany wieloma czynnikami. Wiedza dotycząca budowy morfologicznej, specyficznej dla różnych dyscyplin sportowych ułatwia proces selekcji. Predyspozycje somatyczne są związane z różnymi możliwościami funkcjonalnymi sportowców. Celem niniejszej pracy było porównanie budowy ciała siatkarzy w zależności od ich poziomu sportowego. Materiał badawczy stanowiły pomiary siatkarzy grających w I i II lidze w Polsce (n=30). Grupę porównawczą stanowiło 15 mężczyzn reprezentujących klub AZS przy Akademii Wychowania Fizycznego. Do analizy wykorzystano następujące pomiary antropometryczne: wysokość ciała (B-v), długość kończyn dolnych (B-sy), wysokość siedzeniową (B-vS), rozpiętość ramion (da3-da3), szerokość barków (a-a), szerokość bioder (ic-ic), masę ciała, obwody i fałdy skórno-tłuszczowe tułowia i kończyn. Wartości cech wysokościowych i długościowych były podobne w obu grupach. Obwody tułowia i ramienia były znacząco niższe u siatkarzy AZS. Natomiast fałdy skórno-tłuszczowe pod łopatką i nad tricepsem były istotnie wyższe w tej grupie. Przedstawione wyniki wskazują, że budowa ciała jest powiązana z efektywnością sportową siatkarzy. Key words: somatic build; volleyball; sport level. Abstract Success in performing professional sports is determined by many factors. Knowledge of morphological body build specific to different sport disciplines facilitates a pre-selection process. Somatic build is often related with different functional abilities of athletes. The aim of this research was to compare body build of volleyball players according to their level of sport. The research material constituted measurements of 1st and 2nd league volleyball male players (n=30). The comparative group consisted of 15 academic volleyball male players from the University School of Physical Education. The following anthropometric measurements were taken: body height (B-v), leg length (B-sy), sitting height (B-vs), arm span (da3-da3), biacromial diameter (a-a), biiliocristal diameter (ic-ic), body mass, and circumferences and skinfolds of trunk and limbs. The values of height and length were similar in both groups. Circumferences of trunk and arm were significantly lower in the academic volleyball players. However subscapular and triceps skinfolds were significantly higher in this group. Presented results indicate that body build is important for the sport level of volleyball players.